Percursos para novas imagens: a produção audiovisual por não videntes - Maia, Renato (2011)
The purpose is to write a reflection on the audiovisual production by the visually impaired. The starting point for this research was a documentary video production workshop offered by the Instituto de Educação e Reabilitação de Cegos do Rio Grande do Norte - IERC / RN, with the participation of blind people with low vision and sighted employees of the institution. The research approach follows the precepts of complex thinking, where work is woven into the network, along with the researched. The theoretical framework is based on the theory of French sociologist Edgar Morin, and other important thinkers for this work, namely: Erving Goffman, Paulo Freire, Michel Foucault, Edward Said, Jacques Aumont, Phillpe Dubois, as well as scholars who think and theorize about his own condition and conduct discussions on the issue of blindness: Francisco Jose de Lima, Evgen Bavcar Jacques Lusseyran and Joana Belarmino. The research was formulated based on the statement in the interest of respondents to understand and produce visual images using video as a tool. In this sense, the methodology adopted approaches of action research in constructing the text and dialogue with the participation of those involved in the project. The technique of gathering the information was based on ethnographic description describing the dynamics of the workshop, the relationships between participants, relationship to the other that sees and the manner of operation of equipment. The main focus is the relationship based on dialogue of information, attitudes and ways of knowing from experience and capacity developed and obstacles for blind people to produce visual images using other benchmarks, such as touch, smell and time dimension and space, and add references that give new meaning to the guidelines based on visuality of ministering to the workshop. It is also held to discuss aspects related to the concept of image with sociological reflection about the audiovisual production made by blind people socially constructed and perpetuated by what Edgar Morin called cultural imprinting. Thus we attempted to walk the route with its obstacles and achievements in the production of new images that were seen